Placebo-controlled effect of topical Qust (Costus) oil on postmenopausal women's sexual desire disorder: a double-blind, randomized clinical trial - Akram Fallah; Fattaneh Hashem Dabbaghian; Amirhossein Jamshidi; Elham Akhtari (PAGEPress Publications, 2024)
Decreased libido and anorgasmia are common problems for women after menopause that reduce the quality of life of couples. This study examined the effect of topical Qust oil on sexual desire disorder in postmenopausal women. In this double-blind, randomized, clinical trial, 110 postmenopausal women with decreased sexual desire visiting a Traditional Medicine Center and Hazrat Rasool Akram Hospital (affiliated to Iran University of Medical Sciences) were selected by convenience consecutive sampling and randomly assigned to experimental and control groups. The experimental group received qust oil, while the control group was given a placebo (liquid paraffin); they were instructed to massage the product topically on their pubic area and perineum daily. The sexual function of both groups was assessed and compared before the intervention and four weeks after the intervention using the Female Sexual Function Index. The mean and standard deviation of the improvement of sexual function post-intervention were 37.66±32.52% and 11.96±11.18% in the experimental and control groups, respectively (p<0.001). In terms of the improvement of components of sexual function, a significant difference was observed between the two groups in the sub-scales of sexual desire [57.05±42.99% vs. 21.25±27.85%, p<0.001], arousal, orgasm, and satisfaction (p<0.001 for all); however, no significant difference was observed in terms of lubrication (p=0.25) and pain during intercourse (p=0.776). In postmenopausal women with sexual dysfunction, massaging the pubic area and perineum with qust oil for at least four weeks significantly improves desire, arousal, orgasm, and sexual satisfaction.